Application of energy conversion and integration technologies based on electro-hydraulic hybrid power systems: A review. (15th November 2022) - Yang, Jian; Liu, Bo; Zhang, Tiezhu; Hong, Jichao; Zhang, Hongxin
Graphical abstract: Highlights: Overview for principles, concepts, and operating modes of electro-hydraulic hybrid power systems. Comparative study on hybrid energy source vehicles with integrated hydraulic systems. Electro-hydraulic strategies for various vehicle types and engineering machinery are reviewed. A novel mechanical-electric-hydraulic power coupling system is distinctively introduced. The application field and future research scope of electro-hydraulic technology are prospected. Abstract: Electro-hydraulic hybrid technology has become one of the most critical and advanced branches in new energy and engineering machinery, which is not mature enough in terms of reliability and safety to be comparable with other technologies. The challenge in developing an energy management strategy for electro-hydraulic hybrid vehicles (EHHV) is how to satisfy conflicting control constraints on energy conversion, electrical energy consumption, and hydraulic energy utilization while ensuring that hydraulic energy is fully utilized within a defined driving cycle. This paper summarizes in detail the principles, concepts, and operation modes of electro-hydraulic hybrid systems. Subsequently, comprehensive analysis, comparison, and discussion of EHHV multi-mode working conditions are illustrated in passenger vehicles, commercial vehicles, and engineering machinery. Simultaneously, combining the traditional permanent magnet rotary motor and swashplate axial piston pump/motor to realize the mutual transformation of electric energy, mechanical energy, and hydraulic energy, a novel mechanical-electric-hydraulic power coupling system is introduced. Ultimately, the scope in application areas, energy conversion, and integrated management of redundancy strategies is foreseen. This review is an essential summary of the management and development of the future EHHVs.